Persepsi Konsumen Mengenai Kemiripan 7 Merek Handphone Berdasarkan Dimensi Kualitas dan Model di Kota Jakarta dan Bandung - James R. Situmorang (Jurnal Administrasi Bisnis, 2013)
Since the advent of handphone (HP) as a sophisticated telecommunication equipmentthat HP is currently the most popular telecomunication equipment worldwide. HP aspersonal telecommunication device is a huge market and is still a potential market. InIndonesia as a HP potential market because the population is many, there are manybrands of HP, especially the emergence of HP’s brand made in China in recent years.The objectives of this research was to determine how consumers’ perception of simi-larity between HP’s popular brands in the market based on the dimensions of qualityand models of HP. Consumers are sampled in the city of Jakarta and Bandung each100 people. Data from the completed questionnaires will be analyzed using SPSSsoftware with Multi Dimensional Scaling application.Keywords: Handphone, perception, telecommunication, consumer